PENGARUH MODEL PEMBELAJARAN PJBL (PROJECT BASED LEARNING) TERHADAP KEMAMPUAN BERPIKIR KREATIF SISWA PADA MATA PELAJARAN IPAS DI SDN RANCALABUH KABUPATEN TANGERANG - Aira Apriliani; Saktian Dwi Hartantri; Zamroni (Pendas : Jurnal Ilmiah Pendidikan Dasar, 2025)
The purpose of this study is to ascertain how much the application of project based learning (PjBL) model influences the creative thinking abilities of elementary school students, particularly in the IPAS subject. The research employed a quasi-experimental approach using the Nonequivalent Control Group Design, where two distinct groups were compared to observe the effect of the treatment given. A total of 42 fifth-grade students from SDN Rancalabuh 1 participated in the study, Split equally into two groups, class VB serves as the control group and class VA as the experimental group, with 21 students in each. The data collection instrument consisted of five essay questions that had previously been validated. The pre-test and post-test findings were analyzed using a t-test. There was no significant difference between the two groups prior to the intervention, according to the analysis, which showed that the pre-test t-value was 0.064, which was less than the t-table value of 2.021. But according to the post-test data, the t-value was 3.129, which was higher than the t-table, suggesting a significant difference following the implementation of the PjBL model. These findings indicate that the project-based approach contributes positively to improving pupils' capacity for original thought.